Ajyal Salima a novel public–private partnership model for childhood obesity prevention in the Arab countries - Habib-Mourad, Carla; Hwalla, Nahla; Maliha, Carla; Zahr, Sarah; Antoniades, Karine (Frontiers in Public Health, 2022)
Abstract The prevalence of childhood overweight and obesity among children is on the rise around the world. Meanwhile, comprehensive multi-sectorial approaches have been found to be effective in improving nutritional status among children. Ajyal Salima is a public-private partnership (PPP) school-based nutrition and physical activity intervention program implemented in six Arab countries. Its objective is to promote healthy eating and physical activity habits among 9–11-year-old students. The stakeholders, involved with the implementation of the program, comprised 1) local authorities, ministries of Education and Health, and Non-Governmental Organizations as public partners, 2) The American University of Beirut as the academic / regional scientific partner, and 3) Nestlé as the private partner. The Ajyal Salima program encompasses four coordinated educational components: classroom sessions, family involvement, food service intervention, and training of trainers. The program’s educational material has been culturally adapted to each country’s needs, as well as pilot tested. This paper describes the strategies used to build the PPP framework of Ajyal Salima, and the role of each stakeholder. The Ajyal Salima program is an example of a promising and sustainable comprehensive PPP program to address childhood obesity, that can be exported to other countries in the region and globally.